Combined in-person and tele-delivered mobile school clinic: A novel approach for improving access to healthcare during school hours. (February 2022) - Nelson, Rachel; Bhattacharya, Syamal D; Hart, Sharon
Abstract: Aims: We report a novel pilot project that allows access to healthcare for children and staff at school via a mobile clinic or telemedicine portal connected to the mobile clinic. The objectives of this pilot project were (a) to perform physicals for children not attached to a primary care physician; (b) to provide medical consultations and treatment for acute illnesses of students and staff, and (c) to lower absenteeism rates among students and staff. Methods: In 2013, Ronald McDonald House Charities, a non-profit organization, partnered with Children's Hospital of Erlanger to provide a mobile clinic trademarked Ronald McDonald Care Mobile utilising a large, box-style truck equipped with examination rooms and a telemedicine portal. Initially, starting with three elementary schools in Bradley County, Tennessee, USA, the programme rapidly expanded to include schools in five other participating Tennessee counties. Only three schools in Bradley County have the option of in-person visits. All other schools access care via telemedicine portals. Funding is provided through multiple grants and community partners. If a student does have insurance, the insurance carrier is billed for the visit, but students without insurance are treated free of charge. Prior to the 2018–2019 school year, only limited data were collected. Results: Our first goal was to perform physicals for children not attached to a primary care physician. During the 2018–2019 school year, 28 patients presented for a well-child check. However, 16 of these (57%) did not have a primary care physician. Of note, 19% of students presenting for any complaint did not have a primary care physician on file (172 students). All well-child checks were performed in-person on the Care Mobile. Our second goal was to provide medical consultations and treatment for acute illnesses. A total of 1446 persons were seen for sick visits. Of these, 424 were telemedicine visits (352 students and 72 staff), while 1022 were in-person visits. The five most common diagnoses that the nurse practitioner managed during the 2018–2019 school year included acute pharyngitis, acute upper respiratory infection, streptococcal pharyngitis, fever and acute maxillary sinusitis. Finally, our third goal was to lower absenteeism rates. There were 1446 sick person visits (1253 students and 193 staff). Twenty-two per cent of the students (276 persons) returned to class while 74% (142 persons) of staff returned to work. Conclusion: The mobile/telemedicine health clinic is a novel innovation to increase access to acute care and reduce school absenteeism among both students and staff, potentially saving schools hundreds to thousands of dollars.